Current Clinical Progress of PD-1/PD-L1 Immunotherapy and Potential Combination Treatment in Non–Small Cell Lung Cancer. (December 2019) - Li, Jia-Xin; Huang, Ju-Min; Jiang, Ze-Bo; Li, Run-Ze; Sun, Ao; Lai-Han Leung, Elaine; Yan, Pei-Yu
Conventional methods in treating non–small cell lung cancer contain surgery, chemotherapy, radiotherapy, and targeted therapy, which have various defects. Recently, with the deeper research on tumor immunity, immunotherapy has made the breakthrough in the treatment of cancers. Especially developments of programmed cell death-1/programmed cell death ligand-1 (PD-1/PD-L1) inhibitors bring the therapy into a new stage. This review mainly focuses on introducing existing monoclonal antibodies containing nivolumab, pembrolizumab, atezolizumab, avelumab, and durvalumab, along with 3 ordinary biomarkers such as PD-L1 expression, tumor mutation burden, and microsatellite instability. By understanding the resistance mechanism of anti-PD-1/L1 blockade, research is further improving the survival benefit and expanding the benefit population. So, PD-1/PD-L1 inhibitors begin to be combined with various therapeutic strategies clinically. Discussion and comparison of their effectiveness and safety are also comprehensively reviewed. Meanwhile, we explore the potential, the impact, and mechanisms of combining traditional Chinese medicine with immunotherapy.